Development of an Application-Based Water Meter Reading System for Accuracy and Stability of Customer Bills at Perumda Tirta Patriot, Bekasi City - Asri Fianti Asmar; Erlangga Rahimi; Eddy Soeryanto; Rahma Wadiniwaty; Adam Mukhairil Bachtiar; Irfan Duwiguna Sumitra (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Inconsistencies in water meter reading intervals, which often exceed or fall short of the standard 30 days per month, are believed to be a major cause of unreasonable bill spikes and trigger customer complaints. Therefore, the purpose of this study is to analyze the impact of inconsistent water meter reading intervals on customer bill fluctuations and to propose a system upgrade solution for the meter reading application at PERUMDA Tirta Patriot, Bekasi City. The research method used was a qualitative descriptive case study approach, supported by secondary data in the form of meter reading records and billing histories of customers experiencing significant fluctuations, as well as primary data through in-depth interviews with meter readers, billing staff, and customer representatives. The analysis shows that deviations in the reading intervals (especially those exceeding 30 days) directly result in the calculation of accumulated usage volumes and impact the application of higher progressive tariff blocks, resulting in bill inflation. The implementation of the new system is expected to minimize inconsistencies, improve billing accuracy, and ultimately reduce bill fluctuations, while increasing customer satisfaction and trust in PERUMDA Tirta Patriot, Bekasi City.